Electrostatic Control of the Thermoelectric Figure of Merit in Ion‐Gated Nanotransistors (Adv. Funct. Mater. 37/2021). (9th September 2021) - Prete, Domenic; Dimaggio, Elisabetta; Demontis, Valeria; Zannier, Valentina; Rodriguez‐Douton, Maria Jesus; Guazzelli, Lorenzo; Beltram, Fabio; Sorba, Lucia; Pennelli, Giovanni; Rossella, Francesco
Abstract : Electrolyte Gating In article number 2104175, Domenic Prete, Francesco Rossella, and co‐workers present a boost in thermoelectric energy conversion technology via a novel device platform featuring high aspect ratio semiconductor nanostructures and soft‐matter systems, allowing the simultaneous and all‐electrical benchmark and modulation of the thermoelectric figure of merit: a step forward towards the next generation of nanoscale thermoelectric devices with maximized power generation efficiency.